Bibliometric Analysis of the Management School Principals and the Improvement of Teacher Pedagogy in the Digital Era based on the Scopus Database (1966-2024) - Sutrisno, Shidiq Agung; Sumardjoko, Bambang; Anshori, Ari; Maksum, Muh. Nur Rochim (Universitas Muhammadiyah Surakarta, 2023)
This research aims to identify development mapping and research directions on the Islamic ecosystem in publications listed on the Scopus index. The approach used in this research is bibliometric analysis, which is used to explore all publications indexed in the Scopus database related to